Respuesta :

Step-by-step explanation:

General quadratic equation: y = ax² + bx + c.

When x = 0, y = -3.

=> (-3) = a(0)² + b(0) + c, c = -3.

We now have y = ax² + bx - 3.

When x = 2, y = -4.

=> (-4) = a(2)² + b(2) - 3, 4a + 2b - 3 = -4,

4a + 2b = -1.

Our 1st system of equations is 4a + 2b = -1.

When x = 4, y = -3.

=> (-3) = a(4)² + b(4) - 3, 16a + 4b - 3 = -3,

16a + 4b = 0, 4a + b = 0.

Our 2nd system of equations is 4a + b = 0.

Now we solve the system of equations:

4a + 2b = -1

- (4a + b = 0)

=> b = -1

Hence 4a + (-1) = 0, 4a = 1, a = 1/4. (B)

ACCESS MORE